2020
DOI: 10.1016/j.chemgeo.2020.119584
|View full text |Cite
|
Sign up to set email alerts
|

The use of operationally-defined sequential Fe extraction methods for mineralogical applications: A cautionary tale from Mössbauer spectroscopy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 103 publications
1
21
0
Order By: Relevance
“…Iron speciation measurements were made at the Weizmann Institute of Science using the calibrated extraction of ( 63 ), as modified for application to recent sediments [e.g., ( 64 , 65 )]. The extracted fractions are defined operationally, after ( 66 , 67 ). The first step consists of a 0.5 N HCl extraction for 1 hour, targeting ferrous iron (Fe II ) phases, including AVS, surface-bound Fe II , and Fe II carbonate/phosphate phases.…”
Section: Methodsmentioning
confidence: 99%
“…Iron speciation measurements were made at the Weizmann Institute of Science using the calibrated extraction of ( 63 ), as modified for application to recent sediments [e.g., ( 64 , 65 )]. The extracted fractions are defined operationally, after ( 66 , 67 ). The first step consists of a 0.5 N HCl extraction for 1 hour, targeting ferrous iron (Fe II ) phases, including AVS, surface-bound Fe II , and Fe II carbonate/phosphate phases.…”
Section: Methodsmentioning
confidence: 99%
“…Both studies showed that the hydroxylamine-HCl step after Poulton and Canfield (2005) effectively extracts easily reducible Fe (oxyhydr)oxides when present. However, Hepburn et al (2020) also demonstrated that nontronite, an Fe(III)-rich member of the smectite group, is also dissolved during the hydroxylamine-HCl step. Ryan et al (2008) further observed a partial dissolution of Fe contained in chlorite and smectite of up to 13.5% of bulk Fe even with a less concentrated hydroxylamine-HCl solution (0.5 M) and a shorter reaction time of only 16 h. The hydroxylamine-HCl treatment leads to the reduction of structural Fe(III) in these phyllosilicates, which creates local instabilities in crystal energies from charge imbalance, thus, promoting mineral dissolution (Stucki et al, 1984).…”
Section: Quantification and Characterization Of Reactive Fe Mineral Phases At Site C0023mentioning
confidence: 99%
“…Our analyses demonstrate that Fe speciation on ancient sediments must be interpreted with caution. As already proposed by Slotznick et al (2020) and Hepburn et al (2020), the application of an independent technique such as rock magnetic analyses or Mössbauer spectroscopy on selected samples is very useful to validate chemical Fe extraction data. The Poulton and Canfield (2005) method was tested on modern fluvial and glacial sediments.…”
Section: Quantification and Characterization Of Reactive Fe Mineral Phases At Site C0023mentioning
confidence: 99%
“…After centrifugation (4000 rpm for 4 min at 21 • C), the supernatant from each extraction was stored at 4 • C until analysis by atomic absorption spectroscopy (AAS). Recent research has shown that mineralogical associations based on sequential chemical extractions need to be treated with caution (Oonk et al, 2017;Slotznick et al, 2020;Hepburn et al, 2020). For instance, the efficacy of the Fe acetate stage in extracting iron bound in carbonates ranges from 3 to 85% (Oonk et al, 2017;Hepburn et al, 2020).…”
Section: Solid Phase Analysesmentioning
confidence: 99%
“…Recent research has shown that mineralogical associations based on sequential chemical extractions need to be treated with caution (Oonk et al, 2017;Slotznick et al, 2020;Hepburn et al, 2020). For instance, the efficacy of the Fe acetate stage in extracting iron bound in carbonates ranges from 3 to 85% (Oonk et al, 2017;Hepburn et al, 2020). The solubility of the targeted minerals depends upon their grain size, crystallinity and mineralogical association (Slotznick et al, 2020).…”
Section: Solid Phase Analysesmentioning
confidence: 99%